Developing online speaking activities via TikTok: project-based learning / Ikhsanudin Ikhsanudin and Dwi Susanto Ali Purwoko - Ikhsanudin, Ikhsanudin; Ali Purwoko, Dwi Susanto (Universiti Teknologi MARA, Pulau Pinang, 2022)
The COVID-19 pandemic has changed the youngsters' lifestyles from offline to online. Short movies, such as TikTok, have become famous for communications and entertainment. This article describes a perspective of developing instructions under Project-Based Learning (PBL/PjBL) approach. In this article researchers suggest TikTok media as the platform of creating videos. Our literature review revealed that TikTok has many facilities that can help language teaching and learning, particularly in the speaking skill, and can be used to support PBL. Teenagers who are currently studying in high school use social media such as videos or links of videos intensively. They can learn many types of texts and how to communicate in different situations from videos available on the internet or by producing and uploading videos. Our design of online TikTok English speaking PBL instruction consists of teachers, learners, and materials that support one another. The seven steps in the design indicate that learning should be conducted through exploration, creation, and collaboration that promote acquisition and supported by scaffolding. The teachers, learners, and materials should synergize to create interactions that stimulate the learners' cognitive, affective, and behavioural domain of learning. Through appropriate social media, the teacher should be able to motivate, advice, guide, facilitate, and evaluate the learners' project activities that consist of planning, organizing, actuating, and controlling.